GUNA-GUNA DAN REALITAS SOSIAL HINDIA BELANDA 1880-1930 - Teguh Hindarto (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Guna-Guna is a magical practice that has been going on for a long time, not only in the present but has been going on since the colonial era. It is very possible that the practice of guna-guna has had strong roots in people's lives before the arrival of Europeans and the occurrence of colonization in the Dutch East Indies. The phenomenon of guna-guna became a symptomatic practice in the colonial era and made Dutch people living in the Dutch East Indies experience an encounter with other aspects of a culture in the Indies. Cultural encounters through the phenomenon of guna-guna that spread in the community led to a number of responses and reactions ranging from discussions in community discussion forums, tonil performances and the publication of witch-themed romances. The phenomenon of guna-guna entered the life of the Dutch in the Indies through various channels of various social classes ranging from housemaids, nyai alias mistresses from the natives, business colleagues, colleagues of government employees, etc. This article places the phenomenon of guna-guna as part of a social fact – using the sociological concept of Emile Durkheim – which has attached itself to the socio-cultural life of the Indies community and as an external force that has brought a number of influences in various fields of life ranging from the formation of public knowledge, the emergence of distinctive vocabulary , performing arts and publishing a number of novels with the magical nuances of the Indies. Through qualitative research methodologies – literature review and text analysis of colonial documents in the form of newspapers and advertisements as well as romances – the phenomenon of guna-guna is analyzed from a number of selected cases and observes the development of terms and their impacts to get a picture of the social reality of the Dutch East Indies society in the colonial era.